Active Site Studies on Microsomal Aminopeptidase - Pickering, Darryl (My University, 1985)
The active site of porcine kidney microsomal aminopeptidase was investigated using single, multiple and EDTA inactivation kinetic studies. Good inhibitors invariably contained a zinc-coordinating group such as the mercapto moiety, which proved to be the best ligand for aminopeptidase. Due to the potency of β -mercaptoethylamine, derivatives of this compound were examined for aminopeptidase inhibition. (S)-2-amino-4-methyl-l-pentanethiol (L-leucinthiol) exhibited the largest potency and specificity towards aminopeptidase when compared against carboxypeptidase A and thermolysin, two similar zinc-peptidases. The presence of a zinc-coordination subsite, two hydrophobic pocket subsites and a second amine-binding subsite (distinct from that responsible for substrate recognition) were discerned and the binding modes of amino acid hydroxamates and mercaptoamines compared using Yonetani-Theorell inhibition kinetics. Aminopeptidase does not show virtually any stereoselectivity between L-and D-leucine hydroxamate while greater than a 1,000-fold preference is seen for L-leucinthiol over the D isomer. Also, the amino group of mercaptoamines is crucial to the binding of these inhibitors whereas that of the hydroxamate compounds does not seen to contribute much to their binding. The differences in binding between hydroxamates and mercaptoamines are postulated to be a consequence of the product analogue nature of the former and transition state analogue character of the latter. L-leucine hydroxamate is proposed to bind in a backwards orientation while the D isomer binds in the normal substrate-like position. Similarly, L-leucinthiol is proposed to bind in the same fashion as substrate. Design of future inhibitors should endeavour to: (1) lower the pᵏₐ of the α-amino group, (2) include an extended chain structure capable of binding to additional hydrophobic pockets, (3) incorporate a second amine moiety into the structure to interact with the second amine-binding subsite and (4) replace the mercapto group with a more potent zinc ligand such as the selenol group.
Keywords: microsomal; aminopeptidase; active site; active; porcine; pig